1976
DOI: 10.19182/remvt.7994
|View full text |Cite
|
Sign up to set email alerts
|

Portage de Salmonella chez Testudo sulcata, tortue terrestre du Sénégal

Abstract: Une enquête épidémiologique est effectuée sur le portage chronique de Salmonella chez une tortue africaine Testudo sulcata. 30 prélèvements d'excréments ont permis de mettre en évidence 6 sérotypes: S. oranienburg, S. corvallis, S. durban, S. ilandoff, S. bahrenfeld, S. adelaïde. S. bahrenfeld est isolé pour la première fois au Sénégal. Les possibilités de contamination de l'homme et d'espèces animales domestiques sont envisagées

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Serotypes isolated during these studies were very similar to the serotypes found by Corsalini in Italy in 1975, less similar to those found by Greenberg and Sechter in Israel in 1992, and not at all similar to the types identified by Doutre and Boche in Senegal in 1976. This may indicate that the occurrence of Salmonella serotypes in tortoises is associated with specific geographical regions.…”
Section: Species Male* Female + Male ‐ Female ‐ Total + Total ‐supporting
confidence: 54%
See 1 more Smart Citation
“…Serotypes isolated during these studies were very similar to the serotypes found by Corsalini in Italy in 1975, less similar to those found by Greenberg and Sechter in Israel in 1992, and not at all similar to the types identified by Doutre and Boche in Senegal in 1976. This may indicate that the occurrence of Salmonella serotypes in tortoises is associated with specific geographical regions.…”
Section: Species Male* Female + Male ‐ Female ‐ Total + Total ‐supporting
confidence: 54%
“…These animals may carry the agents in the intestinal tract without showing any clinical signs. A large variety of Salmonella serotypes have been isolated from tortoises (Ozsan and others 1973, Corsalini 1975, Doutre and Boche 1976, Greenberg and Sechter 1992 and tortoises, therefore, constitute a potential source of zoonotic disease in human beings (Lamm and others 1972, Tauxe and others 1985, Giljahn 1986, Ackman and others 1995, Woodward and others 1997. Most epidemiological studies concerning salmonellosis in tortoises have been performed in free-living species and in farm-bred aquatic turtles; moreover, most investigations have been conducted in the USA.…”
mentioning
confidence: 99%
“…Besides chicken, Salmonella has been detected in several food animals in Senegal, including small ruminants [54], beef [55], and swine [56]. Additionally, Salmonella is well spread in Senegalese wildlife species and has been detected in vulture [57], bats [58], and turtles [59]. This endemic presence and the diversity of serovars that can cause clinical infection in humans represent an important public health concern in context of the rising frequency of iNTS in sSA [11].…”
Section: Animal Reservoir Of Salmonella and Invasive Nontyphoidal Sal...mentioning
confidence: 99%